Microbiota transplantation for cotton leaf curl disease suppression—core microbiome and transcriptome dynamics - Ayesha Badar; Rhea Aqueel; Ali Nawaz; Umer Zeeshan Ijaz; Kauser Abdulla Malik (Communications Biology)
Abstract Microbiota transplantation is a strong tool for managing plant disease. This study investigates the effects of microbiota transplantation on Cotton Leaf Curl Disease (CLCuD) resistance in Gossypium hirsutum, a species with good fiber length but high susceptibility to biotic stresses. Using metabarcoding for V3-V4 16S rRNA gene amplicon, microbial fractions from both rhizosphere and phyllosphere of CLCuD-resistant species Gossypium arboreum, and susceptible cotton varieties are analyzed. Unique bacterial taxa have been identified associated with disease resistance. Interspecies and intraspecies microbiota transplantation is conducted, followed by CLCuD incidence assays. It is seen that rhizospheric microbiota transplantation from G. arboreum FDH228 significantly suppresses CLCuD in G. hirsutum varieties, outperforming exogenous salicylic acid application. While phyllospheric transplants also reduce disease incidence, they are less effective than rhizospheric transplants. Differential expression analysis DESeq2 is utilized to identify key bacterial genera correlated with CLCuD suppression, including Pseudoxanthomonas and Stenotrophomonas in the rhizosphere of G. arboreum FDH228. Functional pathway analysis reveals upregulation of stress response and metabolism in tolerant species. Transcriptomics reveals upregulation of genes involved in protein phosphorylation and stress response in interspecies rhizospheric microbiota transplants. This study highlights microbiota transplantation as a sustainable method for controlling CLCuD along with specific microbial and genetic mechanisms contributing to CLCuD resistance.